Диагностика линий электропередач при помощи летательного аппарата повышенной дальности действия - Горюшко, Вадим Вадимович; Лищина, Владислав Владимирович; Данильченко, Дмитрий Алексеевич; Ткачов, Юлий Витальевич; Безкостный, Павел Игоревич; Яковенко, Иван Сергеевич; Якименко, Иван Владимирович; Переверзев, Богдан Геннадиевич (Національний технічний університет "Харківський політехнічний інститут", 2018)
В статье рассмотрены возможности диагностики воздушных линий электропередач с помощью беспилотных летательных аппаратов. Были проанализированы различные типы летательных аппаратов, их недостатки и преимущества. По результатам анализа, для коптеров был выявлен общий недостаток, малая дальность полета и из-за высокой скорости полета БПЛА («самолета») недостаточная точность фиксации параметров линии. Авторами предлагается использование коптеров для мониторинга воздушных линий. Описано оборудование необходимое для мониторинга воздушных линий. Особое внимание уделено зарядному устройству, позволяющему увеличить дальность полета коптера. За счет преобразования энергии электромагнитного поля в электродвижущую силу с последующим выпрямлением полученного тока для питания коптера.

The article considers the possibilities of diagnostics of overhead power lines using unmanned aerial vehicles with extended range. Various types of aircraft, their shortcomings and advantages were analyzed. According to the results of the analysis, for Copters there was a general lack, a short flight range and the need for an operator to control the Copter. Because of the high flight speed of the UAV (the "aircraft"), it is not possible to provide sufficient accuracy of fixing the line parameters and the coordination of the allocation by the air traffic controllers of the flight altitude. The authors propose the use of Copters with the possibility of unmanned flight and recharging from the transmission line with induced voltages for monitoring air lines. The equipment of the copter, necessary for monitoring of overhead lines, is described. Particular attention is paid to the charger, which allows to increase the range of the flight of the Copter. By transforming the energy of the electromagnetic field into an electromotive force and then rectifying the resulting current to supply the copter. The use of such a copter makes it possible to achieve savings in the cost of servicing overhead power lines and substations, reduce the negative effect of the magnetic field on maintenance staff, and increase the safety of maintenance personnel and work crews.
Diagnostics of overhead power lines using unmanned aerial vehicles with extended range
Keywords: коптер; БПЛА; зарядное устройство; наведенные напряжения; copter; UAV; charger; induced voltages